"Fights Happen . . . It's Just What Drunks Do": Alcohol and the Situational Normalization of College Student Fighting. (December 2018) - Weiss, Karen G.; Woods, Joshua
Fights are common at many U.S. residential universities and colleges and often seen as "normal" by students who witness them. This study explores the normalization of college fighting by using a situational learning approach that highlights definitions as learned and shared within a drinking context. Exploratory analysis of survey data finds that nine in 10 fights at college occur when at least one participant is intoxicated, and more than half of fights take place at drinking hot spots (e.g., bars, parties). Fights that occur at drinking hot spots are also twice as likely to be seen as normal (e.g., ordinary, harmless) by students who witness them, even after controlling for the seriousness of the fight (as measured by injury, number, and gender of fighters). Students who drink are four times as likely as nondrinkers to normalize fights. Yet, fights are no more likely to be normalized when fighters or witnesses are intoxicated, suggesting expectations related to intoxication and the drinking context may have a greater impact on definitions than alcohol itself. We conclude with a discussion of the theoretical and practical relevance of situational learning in future research on fighting and violence more broadly.